Unmasking Electoral Turmoil: The General Election Supervisory Agency's Battle Against Disputes in Indonesia’s Democracy - Budi Purwanto; Dina Puji Wahyuni; Ahmad Rafiq Jatihusudo (Universitas Negeri Semarang, 2023)
This paper critically examines the mechanisms employed by the General Election Supervisory Agency (Bawaslu) in Indonesia for resolving election disputes. Focusing on the country’s democratic landscape, where electoral integrity is paramount, the study delves into the procedural framework and legal avenues that the Bawaslu employs to address election-related conflicts. The research explores the historical context and evolution of the Bawaslu's role, shedding light on its establishment, powers, and responsibilities. By analyzing case studies and key instances of election disputes, the paper evaluates the efficacy and responsiveness of the Bawaslu in managing and adjudicating conflicts within the electoral process. Additionally, the study investigates the legal instruments and regulations governing the Bawaslu's dispute resolution functions. This includes an examination of the agency's authority in interpreting electoral laws, handling complaints, conducting investigations, and rendering decisions. The paper scrutinizes the transparency, accountability, and impartiality of the Bawaslu’s decision-making processes. Furthermore, the research assesses the impact of Bawaslu’s decisions on the broader electoral system, considering implications for public trust, political stability, and the overall health of Indonesia's democracy.